A Simple and Cheap Method for Minimizing Thawing and Cooking Losses from Prawns - Mathen, Cyriac (Fishery Technology, 1970)
A dip method for minimising thawing and cooking losses from prawns reported. Though the dip method achieved the primary improving yields without adversely affecting them biochemically and organoleptically, it has the disadvantages that the treatment cost is high and that an additional step is necessary in the processing line. These disadvantages are overcome in a modified method. The standardisation of the modified method is the subject of this communication. The method offers several advantages such as decreased loss of prawn during thawing, low cost, requirement of low dimensions of cartons, and soluble water extractable nitrogen.